Light-transmitting material

By introducing molecule A with a specific structure into the curing agent of the light-transmitting material, the problem of insufficient wear resistance and light transmission of existing light-transmitting materials is solved, and a light-transmitting layer with high light transmittance and excellent wear resistance is achieved. Improved the performance of the detection equipment.

CN119431707APending Publication Date: 2025-02-14HUAWEI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310972739.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When the conventional light-transmitting material forms a light-transmitting layer, it lacks wear resistance and is prone to damage, and has insufficient light-transmitting properties, which affects the transmission of light and reduces the detection effect of the detection equipment.

Method used

By introducing molecule A into the curing agent, the composition of molecule A comprises at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups, increasing the crosslinking degree and transparency of the light-transmitting material, thereby improving the light-transmitting layer wear resistance and light transmittance.

Benefits of technology

The light-transmitting layer has high light transmittance and excellent wear resistance, and improves the service life and detection effect of the detection equipment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, in particular to a light-transmitting material which comprises an isocyanate-terminated polyurethane prepolymer and a curing agent, wherein the curing agent comprises a molecule A, and the molecule A comprises at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups. The light-transmitting material provided by the invention comprises the molecule A, the molecule A comprises at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups, and the crosslinking degree of the light-transmitting material can be increased by introducing three or more functional group molecules, so that the wear resistance is improved; and the introduction of asymmetric functional groups can reduce the crystallization of the light-transmitting material and increase the transparency of the light-transmitting material, so that the light-transmitting layer prepared from the light-transmitting material has high light transmittance and excellent wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a light-transmitting material. Background Art

[0002] Translucent materials can be used to form translucent layers, which can be used in various detection devices that require a translucent path, such as laser detection equipment. However, when existing translucent materials are used to form a translucent layer, the translucent layer has insufficient wear resistance and is easily damaged during use; moreover, the insufficient light transmittance of the translucent layer will also affect the transmission process of light, thereby reducing the detection effect of the equipment. Summary of the invention

[0003] In view of this, the present application provides a light-transmitting material, which has good light transmittance and wear resistance due to the special structure of molecule A in the curing agent.

[0004] The present application provides a light-transmitting material, which includes an isocyanate-terminated polyurethane prepolymer and a curing agent; wherein the curing agent includes a molecule A, and the composition of the molecule A includes at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups.

[0005] In the above scheme, the composition of molecule A includes at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups. The introduction of three or more of the above functional group molecules can increase the cross-linking degree of the light-transmitting material, thereby increasing the wear resistance; and the introduction of asymmetric functional groups can also reduce the crystallization of the light-transmitting material and increase the transparency of the light-transmitting material, so that the light-transmitting layer prepared by the light-transmitting material has both high light transmittance and excellent wear resistance.

[0006] In some embodiments, the light-transmitting material has at least one of the following characteristics:

[0007] (1) The mass percentage of the molecule A in the light-transmitting material is 1% to 30%;

[0008] (2) The mass percentage of the molecule A in the light-transmitting material is 3% to 20%.

[0009] In the above scheme, the curing agent contains molecule A, and the special structure of molecule A can increase the transmittance and wear resistance of the light-transmitting material. If the mass percentage of molecule A in the light-transmitting material is too low, the wear resistance and light transmittance of the light-transmitting material will be reduced, and the mass percentage of the isocyanate-terminated polyurethane prepolymer is too high, resulting in an increase in the flexibility of the light-transmitting layer prepared from the light-transmitting material, and the light-transmitting layer is prone to deformation during use; if the mass percentage of molecule A in the light-transmitting material is too high, the mass percentage of the isocyanate-terminated polyurethane prepolymer is too low, and the light-transmitting layer prepared from the light-transmitting material does not have sufficient elastic properties, that is, the brittleness of the light-transmitting layer increases, and the light-transmitting layer is easily damaged when a slight deformation occurs during use.

[0010] In some embodiments, the light-transmitting material has at least one of the following characteristics:

[0011] (1) The molecule A further comprises a functional group B, wherein the functional group B includes but is not limited to one or more of a halogen atom, a hydroxyl group, an aldehyde group, a carboxyl group, an ester group, a carbonyl group, an ether bond, a carbon-carbon double bond, a carbon-carbon triple bond, an amino group, a peptide bond, a nitro group, an amide group or a cyano group;

[0012] (2) The functional group B is a polar functional group;

[0013] (3) The polar functional group includes but is not limited to one or more of an amide group, a ketone group, an ester group or a cyano group.

[0014] In the above scheme, molecule A also contains polar functional groups. The addition of polar functional groups will increase the glass transition temperature Tg of the light-transmitting material. The higher the glass transition temperature Tg of the light-transmitting material, the higher the hardness of the light-transmitting material, and thus the better the wear resistance of the light-transmitting material.

[0015] In some embodiments, the light-transmitting material may be prepared as a light-transmitting layer, and the light-transmitting layer has at least one of the following characteristics:

[0016] (1) The porosity of the light-transmitting layer is ≤20%;

[0017] (2) The porosity of the light-transmitting layer is ≤10%;

[0018] (3) The porosity of the light-transmitting layer is ≤5%.

[0019] In the above scheme, the porosity of the light-transmitting material will affect the volume density, strength and other properties of the prepared light-transmitting layer. If the porosity of the light-transmitting layer formed by the light-transmitting material is too large, the density of the light-transmitting layer is too small, and the strength of the light-transmitting layer is too low, the wear resistance of the light-transmitting layer will be reduced, and the transmittance of the light-transmitting layer will also be reduced.

[0020] In some embodiments, the light-transmitting material may be prepared as a light-transmitting layer, and the light-transmitting layer has at least one of the following characteristics:

[0021] (1) The density of the light-transmitting layer is 0.7 g / cm 3 ~1.15g / cm 3 ;

[0022] (2) The density of the light-transmitting layer is 0.9 g / cm 3 ~1.15g / cm 3 .

[0023] In the above scheme, if the density of the light-transmitting layer is too small and the strength of the light-transmitting layer is too low, the wear resistance of the light-transmitting layer will be reduced, and the large porosity will cause the transmittance of the light-transmitting layer to also decrease; if the density of the light-transmitting layer is too large and the strength of the light-transmitting layer increases, the wear resistance of the light-transmitting layer will increase, but the difficulty of preparing the light-transmitting layer will increase.

[0024] In some embodiments, the light-transmitting material may be prepared as a light-transmitting layer, and the light-transmitting layer has at least one of the following characteristics:

[0025] (1) The elongation at break of the light-transmitting layer is ≥400%;

[0026] (2) The elongation at break of the light-transmitting layer is ≥500%;

[0027] (3) The elongation at break of the light-transmitting layer is ≥ 600%.

[0028] In the above scheme, if the elongation at break of the light-transmitting layer made of the light-transmitting material is too low, the plasticity of the light-transmitting layer is poor, the light-transmitting layer is difficult to recover after deformation, and the light-transmitting layer is prone to wear, resulting in reduced wear resistance.

[0029] In some embodiments, the light-transmitting material can be prepared as a light-transmitting layer, and the light transmittance of the light-transmitting layer in the wavelength range of 400 nm to 750 nm is ≥50%.

[0030] In the above scheme, if the transmittance of the light-transmitting layer in the wavelength range of 400nm to 750nm is too small, the light loss of the light-transmitting layer during use is large, which is not conducive to the detection process.

[0031] In some embodiments, the light-transmitting material may be prepared as a light-transmitting layer, and the Shore hardness of the light-transmitting layer is 30D-85D.

[0032] In the above scheme, if the hardness of the light-transmitting layer is too low, the wear resistance will be poor and it will be easy to wear out during use; if the hardness of the light-transmitting layer is too high, the preparation cost of the light-transmitting material will increase.

[0033] In some embodiments, the light-transmitting material includes an isocyanate-terminated polyurethane prepolymer and a curing agent; wherein the curing agent includes a molecule A, and the composition of the molecule A includes 1 secondary amine group, 1 primary amine group and 1 hydroxyl group.

[0034] In the above scheme, the component parameters of molecule A are preferably within the above range, and the wear resistance and light transmittance of the light-transmitting material are better. DETAILED DESCRIPTION

[0035] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0036] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0037] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0038] Light-transmitting materials are used to form light-transmitting layers, which can be applied to various detection equipment that require light-transmitting paths, such as laser detection equipment, etc. The light is transmitted or received through the light-transmitting layer, and it plays a certain protective role for the transmitting equipment. However, when the existing light-transmitting materials are used to prepare the light-transmitting layer, the light-transmitting layer has insufficient wear resistance and is easily damaged during use, which affects the service life of the detection equipment; moreover, the insufficient light transmittance of the light-transmitting layer will also affect the transmission or reception process of the light, thereby reducing the detection effect of the equipment.

[0039] In view of this, the present application provides a light-transmitting material, which includes an isocyanate-terminated polyurethane prepolymer and a curing agent; wherein the curing agent includes molecule A, and the composition of molecule A includes at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups.

[0040] In the above scheme, the composition of molecule A includes at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups. The introduction of three or more of the above functional group molecules can increase the cross-linking degree of the light-transmitting material, thereby increasing the wear resistance; and the introduction of asymmetric functional groups can also reduce the crystallization of the light-transmitting material and increase the transparency of the light-transmitting material, so that the light-transmitting layer prepared by the light-transmitting material has both high light transmittance and excellent wear resistance.

[0041] In some embodiments, the polyurethane prepolymer terminated with isocyanate in the light-transmitting material can make the light-transmitting layer prepared from the light-transmitting material have elastic characteristics, thereby making the polishing pad have a high elongation at break. The elongation at break refers to the ratio of the maximum elongation of the light-transmitting layer before breaking when stretched to the initial length, which can measure the elongation ability and ductility of the light-transmitting layer under force, and affects the wear resistance of the light-transmitting layer. In addition, after the polyurethane prepolymer is terminated with isocyanate, the cyanate end-capping can couple with the monomer with active hydrogen to form a new chemical bond, increase the molecular weight, and further improve the tensile strength.

[0042] The curing agent in the light-transmitting material plays a curing role when mixed with the isocyanate-terminated polyurethane prepolymer, enhancing the mechanical properties of the light-transmitting layer, such as wear resistance. Specifically, the composition of the molecule A of the curing agent includes at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups. The combination of the secondary amine group, the primary amine group and the hydroxyl group will affect the wear resistance and light transmittance of the light-transmitting material. Optionally, the number of secondary amine groups, primary amine groups and hydroxyl groups in molecule A is different, and the wear resistance and light transmittance of the light-transmitting material are different. Preferably, the curing agent used in the present application includes molecule A, and the composition of molecule A includes at least 1 secondary amine group, at most 1 primary amine group and at most 1 hydroxyl group. It can be understood that the component parameters of molecule A are preferably within the above range, and the wear resistance and light transmittance of the light-transmitting material are better.

[0043] The mass percentage of molecule A in the curing agent of the present application in the light-transmitting material is 1% to 30%. Optionally, the mass percentage of molecule A in the light-transmitting material can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc., or other values ​​within the range. It can be selected according to actual needs and is not limited here. If the mass percentage of molecule A in the light-transmitting material is too low, the wear resistance and light transmittance of the light-transmitting material will be reduced, and the mass percentage of the isocyanate-terminated polyurethane prepolymer is too high, resulting in an increase in the flexibility of the light-transmitting layer prepared from the light-transmitting material, and the light-transmitting layer is prone to deformation during use; if the mass percentage of molecule A in the light-transmitting material is too high, the mass percentage of the isocyanate-terminated polyurethane prepolymer is too low, and the light-transmitting layer prepared from the light-transmitting material does not have sufficient elastic properties, that is, the brittleness of the light-transmitting layer increases, and the light-transmitting layer is easily damaged when a slight deformation occurs during use. Preferably, the mass percentage of molecule A in the light-transmitting material is 3% to 20%. It can be understood that when the mass percentage of molecule A in the light-transmitting material is within the above range, the light-transmitting layer prepared from the light-transmitting material has better wear resistance and light transmittance.

[0044] Further, molecule A also contains functional group B, and functional group B includes but is not limited to one or more of halogen atoms, hydroxyl groups, aldehyde groups, carboxyl groups, ketone groups, ester groups, carbonyl groups, ether bonds, carbon-carbon double bonds, carbon-carbon triple bonds, amino groups, peptide bonds, nitro groups, amide groups or cyano groups, which can be selected according to actual needs and are not limited here; preferably, functional group B is a polar functional group; more preferably, the polar functional group includes but is not limited to one or more of amide groups, ketone groups, ester groups or cyano groups. It can be understood that the addition of polar functional groups will increase the glass transition temperature Tg of the light-transmitting material. The higher the glass transition temperature Tg of the light-transmitting material, the higher the hardness of the light-transmitting material, and thus the better the wear resistance of the light-transmitting material. The glass transition temperature Tg of the light-transmitting material of the present application is ≥60°C, preferably the glass transition temperature Tg is ≥80°C, more preferably the glass transition temperature Tg is ≥120°C, and more preferably the glass transition temperature Tg is ≥149°C.

[0045] In some embodiments, the light-transmitting material can be prepared as a light-transmitting layer. It can be understood that the light-transmitting layer is a solid layer structure formed after the light-transmitting material solidifies. The preparation method includes:

[0046] The isocyanate-terminated prepolymer is reacted with a curing agent, and after being fully stirred at room temperature, the curing agent is cured to obtain a light-transmitting layer; wherein the curing agent contains 1% to 30% of molecule A.

[0047] It should be noted that in the above preparation method, the isocyanate-terminated prepolymer and the curing agent are liquid reactants, so a curing process is required. The curing temperature and time can be selected according to the actual amount of the reactants and are not limited here. If the curing temperature is too high or the curing time is too long, the prepared light-transmitting layer will shrink and crack. If the curing temperature is too low or the curing time is too short, the hardness of the prepared light-transmitting layer will not meet the required requirements, resulting in reduced wear resistance. Preferably, the curing temperature of the light-transmitting layer is 25°C to 120°C, and the curing time of the light-transmitting layer is 1min to 12h.

[0048] Moreover, during the preparation process, the porosity of the light-transmitting layer is controlled to be ≤20%. Optionally, the porosity of the light-transmitting layer can be specifically 20%, 17%, 14%, 11%, 8%, 5%, 3%, etc., or other values ​​within the range. It can be selected according to actual needs and is not limited here. The porosity of the light-transmitting material will affect the volume density and strength and other properties of the prepared light-transmitting layer. If the porosity of the light-transmitting layer formed by the light-transmitting material is too large, the density of the light-transmitting layer is too small, and the strength of the light-transmitting layer is too low, the wear resistance of the light-transmitting layer will be reduced, and the transmittance of the light-transmitting layer will also be reduced. Preferably, the porosity of the light-transmitting layer is ≤5%. It can be understood that the porosity within this range is low and the transmittance of the light-transmitting layer is good.

[0049] The density of the light-transmitting layer is 0.7 g / cm 3 ~1.15g / cm 3 Optionally, the density of the light-transmitting layer may be 0.7 g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 If the density of the light-transmitting layer is too small, the strength of the light-transmitting layer is too low, which will reduce the wear resistance of the light-transmitting layer, and the high density will also reduce the transmittance of the light-transmitting layer; if the density of the light-transmitting layer is too large, the strength of the light-transmitting layer will increase, which will increase the wear resistance of the light-transmitting layer, but the difficulty of preparing the light-transmitting layer will increase. Preferably, the density of the light-transmitting layer is 0.9 g / cm 3 ~1.15g / cm 3 .

[0050] In some embodiments, the light-transmitting layer obtained by controlling the above parameters has the characteristics of both wear resistance and good light transmittance.

[0051] The elongation at break of the light-transmitting layer is ≥400%. Optionally, the elongation at break of the light-transmitting layer can be 400%, 450%, 500%, 550%, 600%, 650%, etc., or other values ​​within the range. It can be selected according to actual needs and is not limited here. If the elongation at break of the light-transmitting layer prepared from the light-transmitting material is too low, the plasticity of the light-transmitting layer is poor, the light-transmitting layer is difficult to recover after deformation, and the light-transmitting layer is prone to wear, which reduces the wear resistance. Preferably, the elongation at break of the light-transmitting layer is ≥500%; more preferably, the elongation at break of the light-transmitting layer is ≥600%.

[0052] The light transmittance of the light-transmitting layer in the wavelength range of 400nm to 750nm is ≥ 50%. Optionally, the light transmittance of the light-transmitting layer in the wavelength range of 400nm to 750nm can be 50%, 60%, 70%, 80%, 90%, 95%, etc., or other values ​​within the range. It can be selected according to actual needs and is not limited here. If the light transmittance of the light-transmitting layer in the wavelength range of 400nm to 750nm is too small, the light transmittance loss of the light-transmitting layer is large during use, which is not conducive to the detection process.

[0053] The Shore hardness of the light-transmitting layer is 30D to 85D. Optionally, the Shore hardness of the light-transmitting layer can be 30D, 35D, 40D, 45D, 50D, 55D, 60D, 65D, 70D, 75D, 80D, 85D, etc., or other values ​​within the range. It can be selected according to actual needs and is not limited here. If the hardness of the light-transmitting layer is too low, the wear resistance will deteriorate and it is easy to wear during use; if the hardness of the light-transmitting layer is too high, the preparation cost of the light-transmitting material will increase.

[0054] The following is described in conjunction with specific embodiments:

[0055] Embodiment 1:

[0056] The isocyanate-terminated prepolymer was reacted with a curing agent, stirred at room temperature, and cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent comprises 30% of molecule A, wherein molecule A is N-(2-aminoethyl)-DL-alanine-2-hydroxyethyl ester.

[0057] Embodiment 2:

[0058] The isocyanate-terminated prepolymer was reacted with a curing agent, stirred at room temperature, and cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent contains 15% of molecule A, wherein molecule A is N-[2-(ethylamino)ethyl]-DL-alanine-2-hydroxyethyl ester.

[0059] Embodiment 3:

[0060] The isocyanate-terminated prepolymer was reacted with a curing agent, stirred at room temperature, and cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent contains 1% of molecule A, wherein molecule A is N-[2-(ethylamino)ethyl]-DL-alanine-2-hydroxyethyl ester.

[0061] Embodiment 4:

[0062] The isocyanate-terminated prepolymer was reacted with a curing agent, stirred at room temperature, and cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent contains 0.1% of molecule A, wherein molecule A is N-[2-(ethylamino)ethyl]-DL-alanine-2-hydroxyethyl ester.

[0063] Embodiment 5:

[0064] The isocyanate-terminated prepolymer was reacted with a curing agent, stirred at room temperature, and cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent comprises 50% of molecule A, wherein molecule A is N-[2-(ethylamino)ethyl]-DL-alanine-2-hydroxyethyl ester.

[0065] Embodiment 6:

[0066] The isocyanate-terminated prepolymer was reacted with a curing agent, stirred at room temperature, and cured at 100°C for 24 hours to obtain a porosity of 10% and a density of 0.9 g / cm 3 wherein the curing agent comprises 50% of molecule A, wherein molecule A is N-[2-(ethylamino)ethyl]-DL-alanine-2-hydroxyethyl ester.

[0067] Embodiment 7:

[0068] The isocyanate-terminated prepolymer was reacted with a curing agent, stirred at room temperature, and cured at 100°C for 24 hours to obtain a porosity of 20% and a density of 0.7 g / cm 3 wherein the curing agent comprises 50% of molecule A, wherein molecule A is N-[2-(ethylamino)ethyl]-DL-alanine-2-hydroxyethyl ester.

[0069] Embodiment 8:

[0070] The isocyanate-terminated prepolymer was reacted with a curing agent, stirred at room temperature, and cured at 100°C for 24 hours to obtain a porosity of 30% and a density of 0.5 g / cm 3 wherein the curing agent comprises 50% of molecule A, wherein molecule A is N-[2-(ethylamino)ethyl]-DL-alanine-2-hydroxyethyl ester.

[0071] Embodiment 9:

[0072] Different from Example 1, an isocyanate-terminated prepolymer was reacted with a curing agent, and after being fully stirred at room temperature, the prepolymer was cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent comprises 30% of molecule A, wherein molecule A is 2-[(4,6-diamino-1,3,5-triazacyclohexane-2-yl)amino]ethan-1-ol.

[0073] Embodiment 10:

[0074] Different from Example 1, an isocyanate-terminated prepolymer was reacted with a curing agent, and after being fully stirred at room temperature, the prepolymer was cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent comprises 30% of molecule A, wherein molecule A is 2-({4-amino-6-[(2-hydroxyethyl)amino]-1,3,5-triazacyclohexane-2-yl}amino)ethan-1-ol.

[0075] Embodiment 11:

[0076] Different from Example 1, an isocyanate-terminated prepolymer was reacted with a curing agent, and after being fully stirred at room temperature, the prepolymer was cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent comprises 30% of molecule A, wherein molecule A is N-ethyl-DL-alanine-2-hydroxyethyl ester.

[0077] Embodiment 12:

[0078] Different from Example 1, an isocyanate-terminated prepolymer was reacted with a curing agent, and after being fully stirred at room temperature, the prepolymer was cured at 100°C for 24 hours to obtain a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent contains 30% of molecule A, wherein molecule A is N-methyl-2-hydroxyethylamine.

[0079] Comparative Example 1:

[0080] The difference from Example 1 is that an isocyanate-terminated prepolymer is reacted with a curing agent and cured at 100°C for 24 hours to obtain a film with a porosity of 5% and a density of 1.0 g / cm 3 wherein the curing agent is 4,4'-diamino-3,3'-dichlorodiphenylmethane.

[0081] test:

[0082] The light-transmitting layer obtained in the above experiment was subjected to light transmittance test and wear resistance test respectively.

[0083] Test results:

[0084] Elongation at break / % Light transmittance / % Hardness / D Example 1 745 60 60 Example 2 659 55 53 Example 3 423 40 55 Example 4 306 31 50 Example 5 711 68 65 Example 6 567 42 51 Example 7 442 21 48 Example 8 315 19 39 Example 9 668 57 63 Example 10 706 54 59 Embodiment 11 734 40 57 Example 12 719 45 60 Comparative Example 1 700 20 61

[0085] It can be seen from the test results of Examples 1 to 3 that when the mass percentage of molecule A in the light-transmitting material is 1% to 30%, the light-transmitting layer has both high light transmittance and excellent wear resistance; referring to the test results of Example 4, it can be seen that if the mass percentage of molecule A in the light-transmitting material is too low, the wear resistance and light transmittance of the light-transmitting material will be reduced; referring to the test results of Example 5, it can be seen that if the mass percentage of molecule A in the light-transmitting material is too high, the hardness of the light-transmitting layer is too high, the plasticity is reduced, and the brittleness of the light-transmitting layer is increased, and the light-transmitting layer is easily damaged when a slight deformation occurs during use.

[0086] It can be seen from the test results of Example 1 and Examples 6 to 7 that the light transmittance of the light-transmitting layer will decrease with the increase of the porosity, and therefore the light transmittance of the light-transmitting layer can be improved by reducing the porosity; referring to the test results of Example 8, it can be seen that if the porosity of the light-transmitting layer is too high, the elongation at break, light transmittance and hardness of the light-transmitting layer will decrease, affecting the performance of the light-transmitting layer.

[0087] It can be seen from the test results of Examples 1 and 9 to 10 that when the composition of molecule A contains at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups, the obtained light-transmitting layer has both high light transmittance and excellent wear resistance; referring to the test results of Examples 11 to 12, it can be seen that when the secondary amine group, primary amine group or hydroxyl group contained in molecule A is missing, the light transmittance of the light-transmitting layer will decrease.

[0088] It can be seen from the test results of Example 1 and Comparative Example 1 that, compared with the light-transmitting layer prepared from the existing light-transmitting material, the introduction of three or more of the above-mentioned functional group molecules in the present application can increase the cross-linking degree of the light-transmitting material, thereby increasing the wear resistance; and the introduction of asymmetric functional groups can also reduce the crystallization of the light-transmitting material and increase the transparency of the light-transmitting material, so that the light-transmitting layer prepared from the light-transmitting material has both high transmittance and excellent wear resistance.

[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A light-transmitting material, characterized in that: The light-transmitting material comprises an isocyanate-terminated polyurethane prepolymer and a curing agent; wherein the curing agent comprises a molecule A, and the composition of the molecule A comprises at least one secondary amine group, at most two primary amine groups and at most two hydroxyl groups.

2. The light-transmitting material according to claim 1, characterized in that: The light-transmitting material has at least one of the following characteristics: (1) The mass percentage of the molecule A in the light-transmitting material is 1% to 30%; (2) The mass percentage of the molecule A in the light-transmitting material is 3% to 20%.

3. The light-transmitting material according to claim 1, characterized in that: The light-transmitting material has at least one of the following characteristics: (1) The molecule A further comprises a functional group B, wherein the functional group B includes but is not limited to one or more of a halogen atom, a hydroxyl group, a keto group, an aldehyde group, a carboxyl group, an ester group, a carbonyl group, an ether bond, a carbon-carbon double bond, a carbon-carbon triple bond, an amino group, a peptide bond, a nitro group, an amide group or a cyano group; (2) The functional group B is a polar functional group; (3) The polar functional group includes but is not limited to one or more of an amide group, a ketone group, an ester group or a cyano group.

4. The light-transmitting material according to claim 1, characterized in that: The light-transmitting material can be prepared as a light-transmitting layer, and the light-transmitting layer has at least one of the following characteristics: (1) The porosity of the light-transmitting layer is ≤20%; (2) The porosity of the light-transmitting layer is ≤10%; (3) The porosity of the light-transmitting layer is ≤5%.

5. The light-transmitting material according to claim 1, characterized in that: The light-transmitting material can be prepared as a light-transmitting layer, and the light-transmitting layer has at least one of the following characteristics: (1) The density of the light-transmitting layer is 0.7 g / cm 3 ~1.15g / cm 3 ; (2) The density of the light-transmitting layer is 0.9 g / cm 3 ~1.15g / cm 3 .

6. The light-transmitting material according to claim 1, characterized in that: The light-transmitting material can be prepared as a light-transmitting layer, and the light-transmitting layer has at least one of the following characteristics: (1) The elongation at break of the light-transmitting layer is ≥400%; (2) The elongation at break of the light-transmitting layer is ≥500%; (3) The elongation at break of the light-transmitting layer is ≥ 600%.

7. The light-transmitting material according to claim 1, characterized in that: The light-transmitting material can be prepared as a light-transmitting layer, and the light transmittance of the light-transmitting layer in the wavelength range of 400nm to 750nm is ≥50%.

8. The light-transmitting material according to claim 1, characterized in that: The light-transmitting material can be prepared into a light-transmitting layer, and the Shore hardness of the light-transmitting layer is 30D-85D.

9. The light-transmitting material according to claim 1, characterized in that: The light-transmitting material comprises an isocyanate-terminated polyurethane prepolymer and a curing agent; wherein the curing agent comprises a molecule A, and the composition of the molecule A comprises at least one secondary amine group, at most one primary amine group and at most one hydroxyl group.